Estimation of a hedonic price equation with instruments for chicken meat in the UK: Does the organic attribute matter? - Jose Eduardo Ribeiro; Adelina Gschwandter; Cesar Revoredo-Giha (University of Kent, School of Economics, 2019)
Chicken meat consumption has increased substantially in the last decades due to farming and processing intensification and due to perceived health and environmental benefits for consumers. Organic chicken additionally, is perceived to have better taste, lead to higher animal welfare and additional benefits for the environment. Thus understanding consumers' preferences for organic chicken is central for policy-making and market strategies that can shape this market in the future. This paper uses a comprehensive data set of scanned shoppings from UK consumers, to show that they are willing to pay an average premium of 135% for the organic attribute in the case of chicken. In addition, this papercontributes to the literature of environmental valuation, demonstrating that household characteristics can be used as instruments into a GMM approach to a hedonic price model, to address the endogeneity issues usually ignored in this literature.
Keywords: C26; Q18; Q51; 330; Hedonic Pricing Method; Instrumental Variables; Organic Food